METHODS OF TEACHING ENGLISH PHONETICS TO UNIVERSITY STUDENTS (Conference Zone, 2022)
Any language is primarily a sound. Learning any language starts with learning the sounds. We offer you a more detailed acquaintance with sounds in the English language - their pronunciation and designation in transcription. In this article, in the process of teaching English phonetics to university students, there are thoughts and opinions about increasing their competence using modern pedagogical and information-communication methods.